Bioremediation Ability of the Local Isolate Enterobacter cloacae from Disposal Site - Muhammad, Hanaa A.; Subhi, Hanan T.; Sediq, Khalid N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
Illegal dumping is a serious problem that needs to be addressed immediately to preserve human health and the environment as if the pollution that arises from it reaches the groundwater, complications of the remediation processes will increase. To decontaminate the organic and inorganic components, bioremediation seems to be the most environmentally friendly and economically viable technique without further treatment as reported by many studies. In this investigation, samples were taken from the soil of the main dumping area in Koysinjaq in Kurdistan Region of Iraq to determine the most potent bacteria to remediate the existed pollutants. The existence of non-essential minerals and organic compounds in the soil sample was detected using X-ray fluorescence device, and ethane and 1,2-dichloroethane solvents separating technique, respectively. Then, from the same samples, three different naturally occurring bacteria were isolated and cultured under optimized conditions then stimulated for a good result. Finally, spectrophotometer was set at wavelength of 600 nm and used to detect the heaviest growth of bacteria after incubating the cultured bacteria on a mineral salt broth medium with the extracted pollutants at pH 7.0 overnight at 32°C. Based on the highest absorbance, the most effective type of bacteria (Enterobacter cloacae) was chosen among others to remediate the organic components in which approximately 90% of them are plastics, medical waste, municipal waste, electrical items, and hydrocarbons, and some heavy metals, for instance aluminum and lead, which were found in the soil.